Visual outcome in patients undergoing penetrating keratoplasty - Singh, Gurpal; Monga, Shamim; Bhandari, Heena; Aggarwal, Varun; Dhingra, Rachna; Jain, Anuj (International Journal of Research in Medical Sciences, 2017)
Background: Penetrating keratoplasty is the surgical removal of diseased cornea with replacement by full thickness corneal donor tissue. The aim of the study was to know the visual outcome in patients undergoing penetrating keratoplasty. Methods:Thirty patients were selected from department of ophthalmology, Guru Gobind Singh medical college & hospital, Faridkot for penetrating keratoplasty. Results:Visual acuity of 6/12 was seen in 1 case, 6/18 in 4 cases, 6/36 in 5 cases, 6/60 in 5 cases, 3/60 in 4 cases, hand movements in 4 cases, PL+PR+ in 2 cases and no perception of light in 2 cases. Final vision at 6 months of follow up was >6/60 in 10 cases (33.33%). 5 cases (16.67%) had vision between 6/60-4/60. 13 cases (43.33%) had vision of 3/60 or less. While in 2 cases (6.67%) there was no vision at the end of follow up. Conclusion:Penetrating keratoplasty helps patients in regaining vision which makes them able to move independently. Although in our study visual outcome of more than 3/60 was present in only 50% cases.